2016
DOI: 10.20546/ijcmas.2016.512.056
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Sensitivity Pattern of Acinetobacter Species Isolated from Clinical Specimens

Abstract: lactamases and aminoglycoside-modifying enzymes (Robert et al., 2006).Although it is considered as one of the commensals of the skin and respiratory tract, it can cause a variety of serious infectious diseases like pneumonia, urinary tract infections, endocarditis, wound infections, meningitis, and septicemia (Peleg et al., 2008). Gram negative bacteria are responsible for more than 30% of hospital

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In a review, the most common sites of infection reported were respiratory tract (45.7% -57.8%), surgical site (27.7%), and catheters or devices (20.5%-25.2%) occurring perioperatively or within the first 12 months of surgery. [25] In our study out of 405 specimens commonly isolated culture positive organisms are Coagulase Negative Staphylococcus 70 (17.3%), Staphylococcus aureus 68 (16.8%), Enterobacter spp. 28 (6.9%), Escherichia.coli 10 (2.5%), Pseudomonas aeruginosa 10 (2.5%), Klebsiella spp.…”
Section: Table 2: Antibiotic Susceptibility Pattern Discussionmentioning
confidence: 60%
“…In a review, the most common sites of infection reported were respiratory tract (45.7% -57.8%), surgical site (27.7%), and catheters or devices (20.5%-25.2%) occurring perioperatively or within the first 12 months of surgery. [25] In our study out of 405 specimens commonly isolated culture positive organisms are Coagulase Negative Staphylococcus 70 (17.3%), Staphylococcus aureus 68 (16.8%), Enterobacter spp. 28 (6.9%), Escherichia.coli 10 (2.5%), Pseudomonas aeruginosa 10 (2.5%), Klebsiella spp.…”
Section: Table 2: Antibiotic Susceptibility Pattern Discussionmentioning
confidence: 60%